THE ANTITUBERCULOSIS DRUG RIFAMPICIN IS ACTIVATED BY 2’, 5’-DIMETHYL BENZOPELARGONOLACTONE FROM THE LEAF OF Coleus atropurpureus L. BENTH - AHYAR AHMAD; MUH. NASRUM MASSI (International Journal of Pharma and Bio Sciences, 2014)
Anti-mycobacterial bioactivity of non polar compounds from Coleus atropurpureus L. Benth was carried out. An cyclic ester terpenoid, 2’, 5’-dimethyl benzopelargonolactone has been isolated from the chloroform fraction from the leaves of Coleus atropurpureus L. Benth, and its structure was determined by spectroscopic evidences including FTIR and 2D NMR and compared to previous data. The in vitro anti-mycobacterial activities of its whole extracts, chloroform extract, and pure compound were evaluated by testing their MIC (minimal inhibitory concentration). The isolate alone was active against M. tuberculosis with MIC at concentration 200 μg/mL, and could also increase the sensitivity of this pathogen to rifampicin drug at concentration 0.5 μg/mL. These studies suggest that anti-mycobacterial 2’, 5’-dimethyl benzopelargonolactone in combination with rifampicin may play an important role for alternative treatment combination against M. tuberculosis strain H37Rv. Further studies aimed to structural modification and semisynthesis of active compound which exhibited increasing anti-mycobacterial activities, need to be carried out in the future.